Groundwater resource directed measures in karst terrain with emphasis on aquifer characterisation in the cradle of humankind near Krugersdorp, South Africa - m.holland@mweb.co.za (University of Pretoria, 2013)
Dissertation (MSc (Engineering and Environmental Geology))--University of Pretoria, 2007.